Some C3-supermagic graphs - Jeyanthi P.,; Selvagopal P.,; Sundaram, S. Soma, (Utilitas Mathematica, 2012)
A simple graph G = (V, E) admits an H-covering if every edge in E belongs to a subgraph of G isomorphic to H. We say that G is Hmagic if there is a total labeling f : V ∪ E → {1,2,3, ⋯ , |V| + E} such that for each subgraph H' = (V', E') of G isomorphic to H, the sum Σ f(v) + Σ f(e) is constant. When f(V) = {1,2, ⋯ , |V|}, then G is vεV' eεE' said to be H-supermagic. In this paper we study C 3-supermagic behaviour of some well known classes of connected graphs.